2022
DOI: 10.1097/shk.0000000000002047
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Phenotyping in Sepsis Using Omics, Functional Analysis, and in Silico Modeling

Abstract: Sepsis is a major health issue and a leading cause of death in hospitals globally. The treatment of sepsis is largely supportive, and there are no therapeutics available that target the underlying pathophysiology of the disease. The development of therapeutics for the treatment of sepsis is hindered by the heterogeneous nature of the disease. The presence of multiple, distinct immune phenotypes ranging from hyperimmune to immunosuppressed can significantly impact the host response to infection. Recently, omics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 58 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…At present, multiple machine learning techniques are being employed in critical care studies. Specific applications include early detection of acute kidney injury, pulmonary embolism, gene expression in sepsis, and leukocyte phenotyping when trying to understand the pathophysiology of sepsis (45)(46)(47)(48)(49). Reinforcement learning has also been used to formulate ICU electrolyte replacement protocols and determine treatment decisions in sepsis (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…At present, multiple machine learning techniques are being employed in critical care studies. Specific applications include early detection of acute kidney injury, pulmonary embolism, gene expression in sepsis, and leukocyte phenotyping when trying to understand the pathophysiology of sepsis (45)(46)(47)(48)(49). Reinforcement learning has also been used to formulate ICU electrolyte replacement protocols and determine treatment decisions in sepsis (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…and the varied composition of systemic leukocytes in both species (humans have higher numbers of circulating neutrophils compared to mice) ( Drake, 2013 ; Efron et al., 2015 ). These factors could significantly alter the trajectory of the disease ( Langston et al., 2023 ). A recent review discussed the repurposing of oncology drugs to treat sepsis and identified several potential compounds (e.g., Topotecan, Olaparib, Trametinib) that are currently being evaluated in sepsis models ( Rumienczyk et al., 2022 ).…”
Section: In Silico Models – Phenotyping Using Omic Methodolo...mentioning
confidence: 99%
“…Machine learning (ML), a branch of Artificial intelligence (AI), can be used to improve sepsis diagnosis, prognosis and clinical/drug monitoring of the disease ( Langston et al., 2023 ). For example, Goto et al.…”
Section: In Silico Models – Phenotyping Using Omic Methodolo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Omics methodologies, including lipomics, proteomics, and transcriptomics, are broad-scale data-intensive techniques that offer a holistic view of biological systems. Langston et al (3) reviewed leukocyte phenotyping in sepsis using omics, functional analysis, and silicon modeling. Omics provides a system-level view through simultaneous analysis of multiple biological pathways.…”
Section: Introductionmentioning
confidence: 99%